Evaluasi Cemaran Lemak Babi Pada Minyak Goreng Sawit Menggunakan Metode Polarisasi Transmisi - heri sugito; Ketut Sofjan Firdausi (Universitas PGRI Semarang, 2018)
This research was conducted for evaluation of contamination of pig fat on vegetable cooking oil using transmission polarization method. The sample used is palm oil that has been contaminated with chicken oil and pork oil, with variations of chicken oil and pork oil content. The light source used is a green laser with a wavelength of 532 ± 10 nm. Measurements are made by observing the change in the transmission polarization angle that occurs when no external electric field is provided and by external electric field generated from two copper plates given a voltage of 0-6 kV. Test results show that palm oil contaminated with pig oil has the greatest change in polarization angle compared to pure palm oil and palm oil that has been contaminated with chicken oil. This is because the content of saturated fatty acids in pig oil is greater than pure palm oil and chicken oil. With these results, the transmission polarization method is expected to become a method for the evaluation of halal of cooking oil.Keywords: Transmission Polarization, Electrooptics, Cooking Oil, Impurities of Lard, Halal